Lost in translation: how neurons cope with tRNA decoding - Guo, Wei; Russo, Stefano; Tuorto, Francesca (Bioessays, 2024)
Post-transcriptional tRNA modifications contribute to the decoding efficiency of tRNAs by supporting codon recognition and tRNA stability. Recent work shows that the molecular and cellular functions of tRNA modifications and tRNA-modifying-enzymes are linked to brain development and neurological disorders. Lack of these modifications affects codon recognition and decoding rate, promoting protein aggregation and translational stress response pathways with toxic consequences to the cell. In this review, we discuss the peculiarity of local translation in neurons, suggesting a role for fine-tuning of translation performed by tRNA modifications. We provide several examples of tRNA modifications involved in physiology and pathology of the nervous system, highlighting their effects on protein translation and discussing underlying mechanisms, like the unfolded protein response (UPR), ribosome quality control (RQC), and no-go mRNA decay (NGD), which could affect neuronal functions. We aim to deepen the understanding of the roles of tRNA modifications and the coordination of these modifications with the protein translation machinery in the nervous system.
Online veröffentlicht: 11. Juli 2024
Gesehen am 21.10.2024